Tools to encourage low-carbon travel - Hine,R (Grantham Institute, 2020)
This discussion paper assesses how different travel incentive schemes affect consumer travel choices, and explores how policymakers and the private sector can support innovative low-carbon incentives to help drive down emissions in the transport sector.